Penerapan Metode Pembobotan ROC Dan Metode WASPAS Pada Sistem Pendukung Keputusan Seleksi Pemilihan Penerima Bantuan UKT - Dito Putro Utomo; Guidio Leonarde Ginting (Journal of Computer System and Informatics (JoSYC), 2022)
The impact of the Covid-19 pandemic that is felt by the community is the paralysis of all daily activities. As a result, the cessation of work for a long time causes the company's economy to cripple and results in many companies losing money and making Termination of Employment (PHK) for employees or employees. For the heads of families, the termination of employment (PHK) experienced, of course, has a fairly heavy impact. There are many bad impacts caused by Termination of Employment (PHK) such as not being able to continue education for children, especially in college due to not being able to pay tuition fees every semester. Therefore, to overcome this problem, the government created a Single Tuition Assistance (UKT) program. However, the UKT assistance provided by the government was not able to cover all the financing needs for students who were affected by the Covid-19 pandemic. Limiting quotas for recipients of Resident Tuition (UKT) assistance for Budi Darma University is a new problem, of course. Decision Support System is a computerized system on a computer that is used to support decision making in organizations. The Weighted Aggregated Sum Product Assessment (WASPAS) method is a combined method consisting of the WP method and the SAW method, the WASPAS method is expected to provide better results in helping to determine the decision support system. To support obtaining optimal and objective results, a weighting method is needed, namely the ROC method. Based on the above discussion, the research that will be carried out is to select students who receive Single Tuition (UKT) assistance. The results showed that the four alternatives with the highest preference scores received UKT assistance, namely A6, A5, A4, A3